Water-energy nexus: Anaerobic co-digestion with elephant grass hydrolyzate. (1st October 2016) - Carvalho, A.R.; Fragoso, R.; Gominho, J.; Saraiva, A.; Costa, R.; Duarte, E.
Abstract: The anaerobic co-digestion process in a continuous stirred-tank reactor (CSTR) was carried out under mesophilic conditions (37 ± 0.2 °C). All the trials were performed at a hydraulic retention time (HRT) of 15 days and the AD reactor was daily fed with a mixture of sewage sludge (SS) and elephant grass hydrolyzate (EGH). In this study, three different trials were assessed, with different mixture proportions of SSSS and EGH: F0 (100:0, v/v), F1 (75:25, v/v) and F2 (50:50, v/v), during 90 days each trial, keeping the organic loading rate (OLR) in a range of 0.94–1.16 g VS L −1 day −1 . The experimental results obtained showed that the soluble chemical oxygen demand (SCOD) removal efficiency was around 77% and 86% for trials F1 and F2, respectively. SS co-digestion with EGH enhanced methane yield, leading to an increment between 23% and 38%, in comparison with the reference scenario (F0). Graphical abstract: Highlights: Mesophilic anaerobic digester performance linked with WTPS and EGH. A 12 L bench-scale reactor operated at mesophilic conditions and 15 days of HRT. A combination of a pretreatment and anaerobic digestion was assessed. The effectiveness of adding easily biodegradable organic matter was confirmed.